Development of next generation adeno-associated viral vectors capable of selective tropism and efficient gene delivery. (February 2016) - Zhang, Chuanling; Yao, Tianzhuo; Zheng, Yongxiang; Li, Zhongjun; Zhang, Qiang; Zhang, Lihe; Zhou, Demin
Abstract: Virus-based nanoparticles have shown promise as vehicles for delivering therapeutic genes. However, the rational design of viral vectors that enable selective tropism towards particular types of cells and tissues remains challenging. Here, we explored structural-functional relationships of the adeno-associated virus 2 (AAV2) vector by expanding its genetic code during production. As a proof-of-principle, an azide moiety was strategically displayed on the vector capsid as a bioorthogonal chemical reporter. Upon bioorthogonal conjugation of AAV2 with fluorophores and cyclic arginyl-glycyl-aspartic acid ligands at certain modifiable sites, we characterized in vitro and in vivo AAV2 movement and enhanced tropism selectivity towards integrin-expressing tumor cells. Targeting AAV2 vectors resulted in selective killing of U87 glioblastoma cells and derived xenografts via the herpes simplex virus suicide gene thymidine kinase, with the potency of ganciclovir being increased by 25-fold. Our results demonstrated successful rational modification of AAV2 as a targeting delivery vehicle, establishing a facile platform for precision engineering of virus-based nanoparticles in basic research and therapeutic applications.